Pengaruh Lingkungan Kerja dan Kepemimpinan terhadap Kepuasan Kerja Pegawai Outsourcing dengan Motivasi Kerja sebagai Variabel Intervening - Mandra Adrika Putra Mandra; Syamsurizaldi; Novera Wandra; Arina Sovia; Vera Septaria; Ipal Istanjung (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the work environment and leadership on job satisfaction of outsourced employees, with work motivation as an intervening variable at PT. Indomarco Adi Prima, Padang Branch. A quantitative approach was used, using the Structural Equation Modeling (SEM) method through SmartPLS 3. The study population was all outsourced employees at PT. Indomarco Adi Prima, Padang Branch, with a sample size of 59 employees selected using census sampling. The data used in this study consisted of primary data (data obtained directly through questionnaires distributed to outsourced employees who served as research respondents) and secondary data (company documents, internal reports, and scientific literature relevant to the research topic). The results showed that the work environment and leadership had a positive and significant effect on job satisfaction. The work environment had a positive and significant effect on work motivation, while leadership had no significant effect on work motivation. Work motivation had no significant effect on job satisfaction.